Evacuation of Swedish survivors after the 2004 Southeast Asian tsunami: The survivors' perspective and symptoms of post-traumatic stress. Issue 2 (March 2019) - Gudmundsdottir, Ragnhildur; Hultman, Christina M.; Valdimarsdottir, Unnur
Aims: Following the 2004 Southeast Asian tsunami, Swedish authorities received public criticism for slow implementation of rescue work. Meanwhile, data are scarce on survivors' perspectives and potential mental health symptoms associated with timing of evacuation. Therefore, the aim of this study was to investigate survivors' contentment with evacuation time and whether duration at disaster site following the 2004 tsunami was associated with post-traumatic stress symptoms (PTSS) and psychological morbidity. Methods: Of 10, 116 Swedish tsunami survivors who returned to Sweden in the first 3 weeks post tsunami, 4910 (49%) answered a questionnaire 14 months later including questions on evacuation time, contentment with evacuation time and PTSS (Impact of Event Scale). We used logistic regression to calculate odds ratios (OR) and 95% confidence intervals (95% CI) of PTSS by timing of evacuation adjusting for gender, age, education, various indicators of trauma exposure and pre-tsunami psychiatric diagnoses. Results: More than half of the survivors (53%) were content with evacuation time while 33% wanted later evacuation and 13% earlier evacuation. Compared with those evacuated 14–21 days post tsunami, individuals evacuated at day 1–4 presented with increased odds of PTSS (crude OR 3.0, 95% CI 2.0–4.5; and multivariable adjusted OR 2.0, 95% CI 1.3–3.0) and impaired mental health (crude OR 1.7, 95% CI 1.2–2.4; and multivariable adjusted OR 1.4 95% CI 1.0–2.0). Conclusions: One-third of Swedish tsunami survivors preferred a later evacuation from disaster sites. These findings call for further studies, with prospective designs, to disentangle the causal direction of the association between evacuation time and PTSS.